INTEGRATING THINK-PAIR-SHARE AND ETHNOMATHEMATICS: LEARNING PLANE AND SOLID GEOMETRY THROUGH EXPLORATION OF SUMENEP GRAND MOSQUE - Adin Lazuardy Firdiansyah; Sitti Karimah Sulfiah; Dewi Rosikhoh; Fatimatuz Zahroh; Nur Hasanah (Universitas Sembilanbelas November Kolaka, 2026)
This study aims to analyze the implementation, effectiveness, and student responses to the Think-Pair-Share (TPS) learning model based on ethnomathematics through exploration of the Grand Mosque of Sumenep. This study used mixed methods with a Sequential Explanatory design. The subjects were 32 10th grade students at MAN 2 Pamekasan. Quantitative data were obtained through pre-tests and post-tests to measure conceptual understanding, as well as questionnaires to measure student responses. Qualitative data were obtained through observation, interviews, and documentation to explore the implementation process and explain quantitative findings. Quantitative data analysis used Paired T-test, while qualitative data analysis used Miles Huberman interactive model. The results of the quantitative study showed a statistically significant increase in students' understanding of geometric concepts, with an average score increasing from 49.03 to 83.81. Qualitative findings explained that this success was supported by main factor, namely the TPS structure, especially the “Pair” stage (discussion in small groups), proved to be a very effective safe zone for students to do peer tutoring and overcome fears experienced by students. It was concluded that the implementation of the ethnomathematics-based TPS model was effective and positive in significantly improving students' understanding of geometric concepts.